Anchorage performance of bolt connection embedded in thin UHPC members. (December 2021) - Lu, Kaiwei; Xu, Qizhi; Wang, Mingdong; Yao, Yiming; Wang, Jingquan
Abstract: Ultra-High-Performance Concrete (UHPC) has the remarkable durability and outstanding mechanical properties such as exceptionally high compressive strength and superior tensile strength. Therefore, the cross section of UHPC structure is generally optimized to make members light and thin. This paper investigated the behavior of single bolt embedded in thin HSC (high strength concrete) and UHPC members under tension loading. Fourteen tension tests were conducted to study the influences of concrete type, embedment depth and diameter of bolt on anchorage performance. The anchorage performance of these anchors embedded in UHPC were significantly improved compared with the bolts in HSC concrete, in both load capacities and displacement capacities. The superior strength and fiber bridging reduced the Angle of fracture, which is approximately 20° to 24°. As a result, the concrete breakout failure area was improved, resulting in an increase in breakout strength and displacement capacity. The test results were discussed in detail to emphasize the influence of concrete splitting on the anchorage performance of bolts embedded in UHPC members. Compared with HSC members, due to the fiber bridging, failure of UHPC members did not happen when splitting. However, the concrete splitting resulted in the decrease of breakout strength. Finally, a splitting modification factor is proposed to predict anchorage strength based on the test results obtained in this paper and others.